ANALISIS PENGARUH MOTIVASI TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (PPAK) (Proceeding Fakultas Ekonomi, 2007)
The discriminative condition in acquiring accountant titte and unfair professionalism level at work market had caused Ikatan Akuntan Indonesia (Indonesian Accountant Association) and DEpartemen Pendidikan dan Kebudayaan (Education and Culture Department) to holf PPAk. The Succes of PPAk should be motivated by accounting student intention in order to improve quality of accounting profession in globalization era. Object in this research were junior and senior students at private universities and state university in Semarang which have >700 student. This research tried to analyzed if motivation might influence accounting student intention to join PPAk programme. Sample in this research amounted 212 questionatre result and it used double linier regression, determinant coefficient, t Test and F test, calassical assumption test, t Test independent test analyze tools. The data analyze gave double regreesion formula, which was: Y=0.154 X1 + 0.150 X2+ 0.103 X3. Quality motivation and career motivation were the most significant factor that influenced accounting student intention to join PPAk that had been tested by t test. Economic motivation did not influence accounting student intention to join PPAk that had been tested by t Test. The F test was used to test overall motivation on student intention which showed that motivation influenced accounting student intention to join PPAk programme. Thre was significant difference between junior students and senior students intention that had been tested by t Test independent test.